RESEARCH OF CHANGES IN BIOCHEMICAL PARAMETERS DURING STORAGE IN APPLES - Комоні, Єва (SWorldJournal, 2022)
The aim of the study was to identify the content and dynamics of titrated acids and vitamin C in different varieties of apples during storage This work presents the results of a research of changes in biochemical parameters in resistant (immune): "Florina